Nascent entrepreneurship: A critical perspective and research agenda in tourism and hospitality - Dias, Á.; González-Rodríguez, M. R.; Hallak, R. (International Journal of Contemporary Hospitality Management, 2023)
Purpose – This study aims to systematize the drivers of nascent entrepreneurship in tourism and to suggest avenues for future research. As a consequence of the pandemic, a reduction in early-stage entrepreneurial activity was reported worldwide. The countries that responded best to this situation were those that fostered entrepreneurship at this early stage, designated as nascent. Hence, research on nascent entrepreneurs requires particular attention. Design/methodology/approach – To address this study’s goal, the authors have examined the development of nascent entrepreneur literature in the last two decades and discussed how the literature on tourism nascent entrepreneurship relates to the mainstream literature in terms of theoretical frameworks. The authors explored specificities of the tourism industry to propose new research avenues to explore the theme of new venture creation in the hospitality and tourism sector. Findings – The authors divided the implication of tourism specificities into main themes: motivations, human and social capital and government and incubators. Several research questions for future research are proposed. Practical implications – By focusing on nascent entrepreneurship, researchers and policymakers can obtain important insights from projects that have not been implemented, going beyond those that have been successfully undertaken, as aimed at in entrepreneurship research. Originality/value – This research contributes to the nascent tourism entrepreneurship literature by providing theoretical and empirical research questions to advance existing knowledge in tourism nascent entrepreneurship.